2015
DOI: 10.1002/2014gl062437
|View full text |Cite
|
Sign up to set email alerts
|

Extending the long‐term record of volcanic SO2 emissions with the Ozone Mapping and Profiler Suite nadir mapper

Abstract: Uninterrupted, global space-based monitoring of volcanic sulfur dioxide (SO 2 ) emissions is critical for climate modeling and aviation hazard mitigation. We report the first volcanic SO 2 measurements using ultraviolet (UV) Ozone Mapping and Profiler Suite (OMPS) nadir mapper data. OMPS was launched on the Suomi National Polar-orbiting Partnership satellite in October 2011. We demonstrate the sensitivity of OMPS SO 2 measurements by quantifying SO 2 emissions from the modest eruption of Paluweh volcano (Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 32 publications
2
85
0
Order By: Relevance
“…and Profiler Suite (OMPS) SO 2 retrievals (Carn et al, 2015) and the Aerocom inventories (Diehl et al, 2012). Figure 3 illustrates the annual mean surface SO 2 simulation using both inventories for year 2010.…”
Section: Geos-5 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…and Profiler Suite (OMPS) SO 2 retrievals (Carn et al, 2015) and the Aerocom inventories (Diehl et al, 2012). Figure 3 illustrates the annual mean surface SO 2 simulation using both inventories for year 2010.…”
Section: Geos-5 Modelmentioning
confidence: 99%
“…SO 2 observations from space-based platforms provide valuable global information on the spatio-temporal patterns 25 of SO 2 emissions that may complement existing bottom-up emission inventories and help to indicate hot spots. Satellite-measured SO 2 has been used to monitor and characterize regional emission trends (van der A et al, 2017), volcanic emissions (Theys et al, 2013;Carn et al, 2016), and anthropogenic emissions from large point sources like smelters (Carn et al, 2007), power plants , and oil sands (McLinden et al, 2012). Additionally, satellite retrievals of SO 2 vertical column densities have been used to quantify the strength of SO 2 emissions 30 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The early eruption was characterized by small to moderate eruptions with gas plumes reaching 6-10 km above sea level (Global Volcanism Program, 2012). Following the first week of the eruption, the continued activity was predominantly effusive (Edwards et al, 2013;Gordeev et al, 2013) and ash and gas plumes were generally constrained to 1-3 km above sea level (Global Volcanism Program, 2012) However, Carn et al (2015) has shown that volcanic SO 2 injections can be decoupled from ash emissions, leading to occasionally misleading plume height reports. Edwards et al (2013) report that 0.06 kt SO 2 was produced during the early eruption phase.…”
Section: The 2012-2013 Eruption Of Plosky Tolbachik Volcanomentioning
confidence: 99%
“…Prior to 2008, OMI provided global daily coverage, but the development of the OMI Row Anomaly (ORA) in late 2008 has led to data gaps in the OMI swath believed to be caused by an obstruction in the sensor"s field of view ( Figure 2). Previous work by Spinei et al (2010) The OMPS instrument suite, launched aboard NOAA"s Suomi-National Polar-orbiting Partnership (SNPP) satellite in October 2011, is also used to measure volcanic SO 2 in the UV (Carn et al, 2015). The OMPS nadir mapper (OMPS-NM) has a lower spatial resolution than OMI with nadir pixel dimensions of 50 x 50 km (Figure 3), except when data are collected in high-resolution mode (once per week on Saturday) with a spatial resolution of 10 x 10 km (Seftor et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation